Sintesis protein mikroba dan aktivitas selulolitik akibat penambahan level zeolit sumber nitrogen slow release pada glukosa murni secara in vitro - Al Qori'ah; Surono Surono; Sutrisno Sutrisno (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2016)
This research aimed to determine the effect of the level of zeolites as slow release nitrogen in pure glucose on microbial protein synthesis and cellulolytic activity. The material used were zeolite of clinoptilolite type with size 40-60 mesh, urea, pure glucose, cow's rumen fluid from RPH Ungaran. The research used completely randomized design (CRD) with 5 treatments and 4 replications. The treatments were T1, T2, T3, T4 and T5 = pure glucose + additional level 2%, 4%, 6%, 8% and 10% of zeolite slow release respectively. Variables observed were microbial protein synthesis and cellulolytic activity. The results showed that the treatment significantly (P<0.05) increased microbial protein synthesis and cellulolytic activity. Results of protein synthesis from higher to lower number were T2 (59.50 mg/ml), T3 (55.58 mg/ml), T4 (47.55 mg/ml), T5 (42.82 mg/ml) and T1 (31.68 mg/ml) respectively. Results of cellulolytic activity from higher to lower number were T5 (3.55 mol ml-1 min-1), T4 (2.36 mol ml-1 min-1), T2 (2.23 mol ml-1 min-1), T3 (2.16 mol ml-1 min-1) and T1 (2.09 mol ml-1 min-1) respectively. The results of microbial protein synthesis and cellulolytic activity at each treatment were in normal level. The addition of the zeolite level as slow release nitrogen source up to 4% increase microbial protein synthesis. Keywords : Zeolites, microbial protein synthesis and activity of cellulolytic